Pengaruh Tata Cahaya Pada Karakteristik Ruang VVIP Hapup, Dstar, Doremi Karaoke - Anastasia Olivia T.Olivia T. (Intra, 2013)
a light system is really an important factor in establishing the atmosphere in the room. The room in which to provide or give an atmosphere or impression that will result in giving a maximum lighting arrangement. With the use of maximum lighting of the room, the room can feel 3D (three dimensional) or feel more alive than the formation of shadows caused by lighting system reflected on the interior elements, color and material of the room. In the use and placement of good lighting system can create an atmosphere and good lighting in the room and the user of the room itself can feel comfortable, with the use and placement of bad lighting system is not good or  not appropriate can give a different impression or opinion of the room as well as the interfere of feeling comfort in the terms of visual and can occur dazzle for the user in the room.